Anonymous sources - Kelly, Mary Louise (Gallery Books, 2013)
"An exciting and entertaining debut international thriller from an NPR correspondent about a terrorist's nuclear threat to blow up the White House. Alexandra James, devoted reporter for the New England Examiner, is attractive, exceptionally smart, an experienced high-end shoe shopper, and used to getting what she wants. When she is assigned to cover the death of a Harvard student doing his year abroad, the whirlwind investigation takes her to Cambridge, London, and then to Washington. The globe-trotting adventures suit her well, as Alex has always been able to talk her way into anywhere, sleep with anyone she fancies, and both out-drink and out-shop her demons. But when the circumstances surrounding the student's death point to something more nefarious than a suicide, Alex the hunter soon becomes Alex the hunted. And she must race to find a dangerous killer before she becomes the next victim"--